Multiple Biomarker Responses in Corbicula fluminea Exposed to Copper in Laboratory Toxicity Tests - Bonnail, Estefania; Buruaem, Lucas M. [UNESP]; Araujo, Giuliana S. [UNESP]; Abessa, Denis M. S. [UNESP]; Angel DelValls, T. (Springer, 2016)
This study evaluated the alteration of the enzymatic system of the freshwater Asian clam exposed to different copper concentrations. Individuals of Corbicula fluminea were exposed to different concentrations of dissolved Cu (0.5, 1, and 2 mg L-1) for 7 days, then, biomarkers of oxidative stress (GST, GPx, GR), exposure (MTs), effect (AChE), and damage (LPO, DNA strand breaks) were quantified. Results showed positive correlations between dissolved metal concentrations and GPx, MTs, and DNA damage, and negative correlation with GST and AChE. In contrast, no clear trend was found for GR and LPO. In general, the established mechanisms of protection might have a beneficial effect on the decreasing ROS attack on membrane and the activation of the metallothioneins. Integrated biomarker analysis revealed that the measured alterations are well correlated with the levels of increasing dissolved copper concentrations in water, demonstrating the effectiveness of this organism for biomonitoring approach purposes.